Exploring EFL Undergraduate Students’ Attitudes towards Learning Writing over Virtual Learning System: A Case Study of Indonesian College Students - Fitria, Eka Nur (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2022)
The study aimed to find out the EFL students’ attitudes toward learning writing over a virtual learning system. The researcher used a qualitative study. There were 46 undergraduate students participating in the study. The data were collected by using a questionnaire and interview sheet through a google form. The result shows that none of the students has a low attitude toward learning writing through online learning, while 58.69% of them have a moderate attitude toward learning writing through virtual learning and the rest of them have a positive attitude toward learning writing over virtual. The interview also reveals that although the students have a moderate attitude toward learning writing online, they see learning writing through online learning as difficult and ineffective while the students who have a high attitude toward learning writing through virtual mostly view learning writing online as interesting, effective, and easy. The students also faced challenges during learning writing through online learning. They are internet connectivity and distraction. The finding also reveals several students’ efforts to improve their writing skills, among others, are reading a lot to get knowledge and ideas, diary writing, and practice writing.